An analysis of the evolutions of the decorative elements: case study the seven dwellings in Ghadames old city / Samira Nuri Ben Said - Ben Said, Samira Nuri (2014)
The Old City of Ghadames in Libya, which is today a major tourist attraction, has some old dwellings that contain intricate and meaningful ornamental art. This thesis seeks to investigate these artistic works and decipher their symbolic meanings. This is because, to the modem generation, even of artists and craftsmen, these meanings are lost and these generations-old artefacts are viewed merely as beautiful visual art. This research seeks to solve this problem and the main objectives are (a) to analyse the roots of the selected traditional decorative motifs in the built environment in Ghadames old city of Libya; (b) to uncover the symbolic meanings of these decorative elements found in the architecture in Ghadames old city; and (c) to provide a deeper understanding of the evolution of traditional decorative elements, and symbols found in selected buildings in Ghadames old city in Libya. Towards this end, the researcher investigated a wide range of such art in various countries of the region to determine the history and influence of early colonial presence by various countries that has left this creative artistic legacy in the Old City of Ghadames. Within the framework of the study, the historical background of Ghadames’s art motifs in architecture and the decorative units are related to various factors including the natural environment and socio-cultural background. The focus is on seven private dwellings from the 16th through 20th centuries. The ornamental art is analyzed and discussed in the context of their historical time and today’s meaning and usage and includes motifs such as the eight-point star, solar motifs, Tree of Life, triangles, jagged lines, rosette or Flower of Life, among many others. The researcher’s investigation of such ornamental art in other countries of the region reveals the many similarities in art, culture and history and presents a vast panoramic view of the wealth of historical endeavors that have impacted the lives and lifestyles of Libyans as well as the peoples of the regional countries who have been similarly touched by their past. This study provides a glimpse of the many religious beliefs and cultural superstitions of not only the people of Ghadames but also of much of the Arab world and allows for better understanding of their socio-cultural commonalities.